The Role of Media Richness in CSR Web Disclosure: The Impact on Users and Organizational Image - Mat Saat, Rafeah; Selamat, Mohamad Hisyam (UUM Press, 2011)
The purpose of this research is to determine whether the richness of corporate social responsibility (CSR) presentation on web disclosure has an impact on user trust, attitude and knowledge regarding such disclosure, and to examine the effect of influenced user’s behavior with richness of CSR presentation toward organization image. This study is expected to contribute towards theory and practice. The first implication, this study contributes to the literature using media richness theory as the framework to put the CSR communication in context. Second, communicating the CSR issues to public is critical to organization especially public listed companies (PLCs) not only because it is required by Bursa Malaysia or compliance by law, but also to encourage organization in delivering the information and gain feedback from stakeholders. This action would make PLCs more engaged in being socially responsible as a corporate citizen to the stakeholders. It can be learnt that the regulatory bodies like Bursa Malaysia and organization hold a particular interest in the findings of this study. The findings can be used to develop appropriate communication strategies and determine the right channel in delivering sustainable value to stakeholders.